Eight Forts. Traces of the Modern in Austro-Hungarian Permanent Fortified Works among the Mountainous South-West Borders of The Empire. 1833-1913 - Paolo Bortot (Histories of Postwar Architecture)
The nineteenth century was a century characterized by numerous wars and geopolitical changes that in fact resulted, by their being politically and geographically unfinished, in the Great War. It characterized the second decade of the twentieth century. The military action, understood, recalling Carl von Clausewitz, as a continuation of politics by other means, led European states to bloody actions of offense and defense predominantly in the plains spaces. This is absolutely evident. In the same period, new considerations of strategy and tactics lead to the consideration of mountainous territory as a place that offers strong positions, in which, as classical history reminds us, a handful of men can stop many: the case of Thermopylae a very famous example. This essay therefore is devoted to eight forts built in the mountainous environment within the Austro-Hungarian Empire with the sole exception of Fort Airolo. These are eight forts that, according to the author, represent milestones in defense in the mountains. These forts, at the same time and in some way, are the works that best represent the attempt to address, according to the logic of their time, the resolution of the problem of modern fortification for the defense of the Empire. The design and practical efforts of the officers of the Austro-Hungarian Genie Corps would eventually lead, in the early 1900s, to the construction of forts made entirely of concrete. Fort Garda was the first. In them we find experimentation with theoretical principles and thoroughly modern construction techniques and materials, making them de facto forerunners of the avant-gardes of modern architecture and in particular of functionalism and brutalism.